Relationship between of coaches’ expectations with instruction and behavior of athletes in football - Fernando Santos (Cuadernos de Psicología del Deporte, 2019)
This study aims to identify the expectations of the coaches on the instruction and behavior of athletes. The second objective is to correlate the expectations of the coaches with the instruction behavior of coaches and with the behavior of athletes in competition. Aiming to achieve these purpose four coaches of youth soccer teams that competed in the national championships in Portugal were studied. We applied observation systems SAIC and SOCAC to encode behaviors of coach's instruction and the behavior of athletes in competition, respectively. To data collection on expectations, the coaches responded to the Questionnaire about Expectations of Instruction and Behavior of Athletes in Competition. The results show that there is short relation between the coach's expectations and what actually happens in competition regarding the instruction behavior and the behavior of athletes.